Economic Instability and Growth: Analyzing the Role Of EPU, Inflation, FDI and Trade on GDP In Eight Asian Countries - Nursam, Nurul Fatmah; Nur Fatiha; Ismail Pulungan; Taosige Wau; Shabur, Usman (Institut Agama Islam Negeri Kendari, 2025)
This study investigates the impact of inflation, foreign direct investment (FDI), trade openness, and economic policy uncertainty (EPU) on gross domestic product (GDP) in eight Asian countries Indonesia, China, Japan, South Korea, India, Pakistan, Thailand, and the Philippines over the period 2014–2023. Utilizing the Generalized Method of Moments (GMM) estimation for dynamic panel data, the results reveal that trade openness has a consistently positive and statistically significant effect on GDP, emphasizing its critical role in sustaining economic growth. FDI also exerts a positive influence, but its statistical significance varies across models, suggesting that differences in institutional capacity may affect its effectiveness. In contrast, inflation shows a negative and significant effect on GDP, indicating that price instability directly hampers growth. Moreover, EPU not only negatively impacts GDP but also significantly moderates the relationship between GDP and both FDI and trade openness, weakening their growth-enhancing effects. These findings highlight the necessity for Asian economies to maintain stable inflation, foster investment-friendly environments, and reduce policy uncertainty to fully harness the benefits of trade and foreign capital inflows.